Judo - Chesterman, Barnaby; Willingham, Bob. (Milwaukee, WI : Gareth Stevens Pub., 2005)
Introduces young students to the basic techniques and training methods of Judo including throws and hold downs, and discusses judo rules, games, and training exercises.
Includes index.
Horn Book, April 2005.
Horn Book.
6.2
3-6
Keywords: Judo -- Juvenile literature; Judo; Martial arts; Judo; Martial arts; Judo; Martial arts